The influence of problem-based learning model and motivation on the learning outcomes of students in the faculty of education at Wisnuwardhana University - Khoirul Efendiy; Indria Kristiawan; Etty Umamy; Abdul Hamid B (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
Student academic achievement is important in education. Low achievement hinders progress and future opportunities. Research shows that factors such as low motivation and mismatched learning models have a negative impact. Learning models play a role in enhancing student engagement and learning outcomes. Understanding these factors is essential to iimprove the iquality iof ieducation. This study evaluates ithe influence iof learning models, student motivation, and their interaction on learning outcomes. Findings indicate that learning models have a isignificant iinfluence ion istudent ilearning ioutcomes. Additionally, student motivation also plays a crucial role in achieving good learning outcomes. The iinteraction ibetween learning imodels iand student motivation also significantly affects ilearning ioutcomes. The implication is that it is important to select the appropriate learning models and enhance student motivation to improve learning outcomes. Further research can explore in more detail the interaction and effects of these factors on student learning outcomes.